68.1k views
2 votes
Which of the following is the solution to the inequality below? -6(4-x)<- -4(x+1)

A. X<- 2
B. X>- 10
C. X>- 2
D. X<- 10

User Dreagen
by
4.4k points

2 Answers

7 votes

Answer:


\sf \: a) \: x < 2

Explanation:

Now we have to,

→ Find the required value of x.

The inequation is,

→ -6(4 - x) < -4(x + 1)

Then the value of x will be,

→ -6(4 - x) < -4(x + 1)

→ -6(4) + 6(x) < -4(x) - 4(1)

→ -24 + 6x < -4x - 4

→ 6x + 4x < -4 + 24

→ 10x < 20

→ x < 20 ÷ 10

→ [ x < 2 ]

Hence, the answer is x < 2.

User Garren S
by
5.7k points
5 votes

Answer:

x<2

Explanation:

To solve the inequality, use the distributive property to simplify the parenthesis. Then use inverse operations to isolate x.

-6(4-x)< -4(x+1)

-24+6x<-4x-4

-24+4+6x<-4x

-20+6x<-4x

-20<-4x-6x

-20<-10x

2>x or x<2


User Peril
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.